Leukemic Presentation of Anaplastic Large Cell Lymphoma: A Diagnostic Challenge Mimicking T-Cell Prolymphocytic Leukemia. Issue 3 (May 2022) - Vadasz, Brian; Wolniak, Kristy; Sukhanova, Madina; Chen, Yi-Hua; Behdad, Amir
Abstract: Anaplastic large cell lymphoma (ALCL) is a rare systemic T-cell neoplasm that typically involves nodal and extranodal sites and is further classified into 2 subgroups: anaplastic lymphoma kinase (ALK-) positive (ALK + ) and ALK-negative. Leukemic presentation of ALCL is extremely rare. Most cases with leukemic presentation are the small-cell variant of ALK + ALCL, are positive for the t(2;5)(p23;q35) translocation, and are associated with a poor prognosis. We report a case of ALK + ALCL that presented with a high white blood cell count and morphologic and phenotypic features resembling T-cell prolymphocytic leukemia.